Utilization of Sludge from the Communal Wastewater Treatment Plant (WWTP) in the Asrama Dinas Lingkungan Hidup (DLH) Jagakarsa of South Jakarta City as Basic Material for Organic Fertilizer - Marsono, Muhammad Ridho; Zahra, Nurulbaiti Listyendah; Sofiyah, Evi Siti (Journal of Sustainable Infrastructure, 2023)
Asrama DLH Jagakarsa has a communal wastewater treatment plant (WWTP) that produces sludge that has not been treated. Asrama DLH residents directly apply the sludge from the communal WWTP as fertilizer for plants. Fecal sludge contains organic substances that provide nutrients to plants. However, there is a possibility that it still contains pathogenic bacteria and metals that can be harmful to plants. This research aims to utilize the fecal sludge from Asrama DLH Jagakarsa WWTP as organic fertilizer with additional ingredients in the form of humic acid. During fertilizer manufacturing, the bacteria and metals are removed. The analysis used includes the composting process conditions analysis, characteristics tests to determine the content of feces and fertilizers, and analysis of the application to plants. Analysis of the conditions in the composting process is the analysis of the pH value of organic fertilizers. Characteristic tests include soil variation (V1), WWTP sludge (V2), and organic fertilizer (V3). Analysis of the application of plant growth was carried out by testing the variation of soil 100% (P1), soil 80% + 20% fecal sludge (P2), and soil 80% + 20% organic fertilizer (P3). The laboratory analysis includes the analysis of nitrogen, phosphorus, potassium (NPP), and water content which will be compared with the quality standard of the Decree of the Minister of Agriculture Number 261 of 2019. The plant that is used as an indicator of the success of organic fertilizer in plant growth is the kale plant. The best value was obtained in the variation of organic fertilizer (V3), namely the NPP content and water content, respectively, which were 4.52%, 2.57%, 0.05%, and 19.84%. This shows that organic fertilizer increases NPP elements and plant growth.